2018
DOI: 10.1074/jbc.ra118.003070
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for (p)ppGpp-mediated inhibition of the GTPase RbgA

Abstract: Efficient adaptation to environmental changes is pivotal for all bacterial cells. Almost all bacterial species depend on the conserved stringent response system to prompt timely transcriptional and metabolic responses according to stress conditions and nutrient depletion. The stringent response relies on the stress-dependent synthesis of the second messenger nucleotides and alarmones (p)ppGpp, which pleiotropically target and reprogram processes that consume cellular resources, such as ribosome biogenesis. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 40 publications
(50 reference statements)
2
44
1
Order By: Relevance
“…Hydrogen-deuterium exchange mass spectrometry (HDX-MS) was essentially conducted as described previously 46,47 . Sample preparation was aided by a two-arm robotic autosampler (LEAP Technologies).…”
Section: Hydrogen-deuterium Exchange Mass Spectrometrymentioning
confidence: 99%
“…Hydrogen-deuterium exchange mass spectrometry (HDX-MS) was essentially conducted as described previously 46,47 . Sample preparation was aided by a two-arm robotic autosampler (LEAP Technologies).…”
Section: Hydrogen-deuterium Exchange Mass Spectrometrymentioning
confidence: 99%
“…mt-LAF4 is bound to H33-35 and appears here to prevent uL2m association. Mt-LAF3 (homolog to the bacterial GTPase RgbA 18 ) is in contact with mt-LAF 5 and 2. However, it is the only GTPase that does not make significant contacts with the rRNA (Fig.…”
Section: Intersubunit Sidementioning
confidence: 99%
“…Given these observations, we wished to identify the component(s) of the translation machinery that is (are) targeted by ppGpp. The translational GTPases EF-Tu, EF-G and IF2 as well as the ribosome associated GTPases including Obg (Buglino et al, 2002; Feng et al, 2014), RsgA (Corrigan et al, 2016; Zhang et al, 2018), RbgA (Corrigan et al, 2016; Pausch et al, 2018), Era (Corrigan et al, 2016), and HflX (Corrigan et al, 2016; Zhang et al, 2018) have all been reported to bind (p)ppGpp. However, (p)ppGpp inhibits protein synthesis by the PURExpress system (Figure 4), which contains only IF2, EF-Tu, and EF-G, so inhibition of one or more of these proteins is likely sufficient to account for the in vivo inhibitory effect of (p)ppGpp on translation.…”
Section: Resultsmentioning
confidence: 99%
“…We show that the (p)ppGpp sensitivity of IF2 can be altered by a specific double mutation in the G1 motif of the G domain, the site of (p)ppGpp binding (Milon et al, 2006). There are numerous examples of other ribosome associated GTPases that bind (p)ppGpp such as ObgE (Buglino et al, 2002; Feng et al, 2014; Persky et al, 2009), BipA (Kumar et al, 2015), RbgA (Corrigan et al, 2016; Pausch et al, 2018), HflX (Corrigan et al, 2016) and Era (Corrigan et al, 2016). Many of these reports demonstrate that (p)ppGpp binding affects their in vitro function in aspects of protein synthesis, such as ribosome assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation